2011
DOI: 10.1515/znc-2011-9-1003
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Compounds from Flowers of Hibiscus rosa-sinensis Linn. and their Inhibitory Effect on Alkaline Phosphatase Enzyme Activity in vitro

Abstract: Graded concentrations (0.1 - 100 mg/mL reaction mixture) of the methanolic extract of the flowers of Hibiscus rosa-sinensis Linn., its water-soluble fraction as well as compounds isolated from this fraction were tested for their inhibitory effect on alkaline phosphatase enzyme activity in vitro. Both the methanolic extract and its water-soluble fraction showed significant inhibitory effects on the enzyme activity in vitro. On screening the activity of the compounds isolated from the water-soluble fraction, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Nine compounds from the active EtOAc fraction were obtained and identified based on melting points and spectral data such as ESI-HRMS, 1 H-NMR, 13 C-NMR, 2D 1 H- 13 C HSQC, and 2D 1 H- 13 C HMBC. These nine compounds isolated and identified in this study can be found in several plant species, and three compounds (taraxerol acetate ( 20 ), p-hydroxybenzoic acid ( 21 ), and quercetin ( 21 )) were previously identified in H. rosa-sinensis . The remaining six compounds are being reported here for the first time in H. rosa-sinensis red flower.…”
Section: Resultsmentioning
confidence: 79%
“…Nine compounds from the active EtOAc fraction were obtained and identified based on melting points and spectral data such as ESI-HRMS, 1 H-NMR, 13 C-NMR, 2D 1 H- 13 C HSQC, and 2D 1 H- 13 C HMBC. These nine compounds isolated and identified in this study can be found in several plant species, and three compounds (taraxerol acetate ( 20 ), p-hydroxybenzoic acid ( 21 ), and quercetin ( 21 )) were previously identified in H. rosa-sinensis . The remaining six compounds are being reported here for the first time in H. rosa-sinensis red flower.…”
Section: Resultsmentioning
confidence: 79%